2017
DOI: 10.3389/fpsyg.2016.02015
|View full text |Cite
|
Sign up to set email alerts
|

Baduanjin Mind-Body Intervention Improves the Executive Control Function

Abstract: This study aims at comparing the effects of the Baduanjin mind-body (BMB) intervention with a conventional relaxation training program on enhancing the executive function. The study also attempts to explore the neural substrates underlying the cognitive effect of BMB intervention using near-infrared spectroscopy (NIRS) technique. Forty-two healthy college students were randomly allocated into either the Baduanjin intervention group or relaxation training (control) group. Training lasted for 8 weeks (90 min/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 40 publications
2
76
0
1
Order By: Relevance
“…They also gathered evidence of significantly raised plasma adiponectin levels associated with the Baduanjin practices, which serves to corroborate with the reduced depression symptoms. Such a reduction in depressive mood was also reported in another eight-week intervention study on healthy college students conducted by Chen, Yue, Tian, and Jiang (2016) [82]; in addition, these researchers demonstrated that Baduanjin could help improve executive function. Similarly, Li et al (2015) [79] also provided some evidence to show that 12-week Baduanjin exercise training (as compared with usual exercises) leads to improved attention, in addition to a couple of physical benefits such as lower limb proprioception, enhanced cardiorespiratory endurance, flexibility, and explosive force of lower limbs.…”
supporting
confidence: 62%
“…They also gathered evidence of significantly raised plasma adiponectin levels associated with the Baduanjin practices, which serves to corroborate with the reduced depression symptoms. Such a reduction in depressive mood was also reported in another eight-week intervention study on healthy college students conducted by Chen, Yue, Tian, and Jiang (2016) [82]; in addition, these researchers demonstrated that Baduanjin could help improve executive function. Similarly, Li et al (2015) [79] also provided some evidence to show that 12-week Baduanjin exercise training (as compared with usual exercises) leads to improved attention, in addition to a couple of physical benefits such as lower limb proprioception, enhanced cardiorespiratory endurance, flexibility, and explosive force of lower limbs.…”
supporting
confidence: 62%
“…Pieramico et al pointed out that multi-modal exercise can be an effective strategy to prevent aging-related cognitive loss, and significant capability of functional and structural changes were maintained in older adults [45]. Other studies have shown that regular physical training may contribute to changes in brain structure [46], brain function [47,48], and alleviate age-related cognitive decline [49]. In the majority of exercise cognition imaging studies, researchers have focused on short-term effects rather than prolonged cognitive benefits of exercise, particularly for motor-cognitive exercise training such as tai chi chuan that is culturally suitable for Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, aunque los programas destinados a la mejora de las funciones ejecutivas en la primera infancia muestran resultados muy positivos, la mayoría de los estudios se centran en niños en edad escolar o universitarios (por ejemplo, Chen, Yue, Tian, y Jiang, 2016;Dias y Seabra, 2016). A pesar del potencial efecto preventivo de la intervención temprana, hasta el momento, sólo un núme-ro limitado de estudios han investigado el efecto de la intervención de las funciones ejecutivas en niños en edad preescolar (3-5 años) (Di Lieto et al, 2017;Sonuga-Barke y Halperin, 2011).…”
Section: Antecedentesunclassified